Light women dancing tango: Gender images as allegories of heterosexual relationships - Carozzi, Maria Julia (2012)
Trying to understand the self-image of Latin American women, many Anglophone studies have turned to the influence of Catholic feminine images, especially the Virgin Mary. Albeit later studies have criticized this emphasis on Marianismo for providing a passive image of women, the prevalence of gender images of Catholic origin continues to dominate research on the continent. Based on 12 years of participant observation in tango milonguero lessons and at night-time milongas in downtown Buenos Aires the author take a different stance on the issue, analysing the image of the ‘light woman’ (la mujer liviana) as an allegorical rendition of heterosexual relationships originating in tango dance halls. This analytical frame is inspired by cultural critiques viewing feminine figures elsewhere as the product of the allegorization and feminization of the relationships of colonizers with the colonized and conquerors with uncultivated lands. However, at odds with this literature, it considers the image under study as emerging from the immediate context where it is exchanged. By showing the resonance of the image of the ‘light woman’ and the characteristics of heterosexual relations in tango social dance events, this article suggests the possibility that gender images may be understood as the feminization and allegorization of relations involving men and women in the very contexts where such images circulate.